USING CANVA TO IMPROVE THE VISUALIZATION OF SOCIAL SCIENCE MATERIALS IN GRADE VII OF SMPN 10 BANDUNG, WEST JAVA PROVINCE - Nia Agustiniar; Fatimah (CV JK Riset Publishing Group, 2025)
This study investigates the effectiveness of Canva platform in enhancing visualization within Social Studies learning among seventh-grade students at SMPN 10 Bandung. Employing a quantitative approach through quasi-experimental nonequivalent control group design, the research encompassed the entire seventh-grade population with random sampling yielding experimental (n=32) and control (n=30) groups. Research instruments comprised multiple-choice objective tests measuring cognitive learning outcomes, observation sheets assessing visualization capabilities, and learning motivation questionnaires. Canva implementation occurred across eight sessions focusing on Indonesia's socio-cultural diversity. Results demonstrated significant differences between experimental and control groups in cognitive learning outcomes (t=6.234, p<0.001), visualization abilities (t=9.847, p<0.001), and learning motivation (t=12.456, p<0.001) with Cohen's d=1.58 indicating large effect size. Delayed post-testing revealed experimental groups retained 89.3% of acquired knowledge compared to 65.7% in control groups. Transfer learning emerged in 72% of experimental students who applied visualization skills across other subjects. Behavioral observations indicated substantial reduction in classroom distractions and enhanced collaborative engagement. The study confirms Canva's efficacy in transforming abstract Social Studies concepts into concrete visual representations, facilitating meaningful learning experiences and sustained knowledge retention. These findings support educational technology integration through user-friendly platforms that democratize digital content creation while maintaining pedagogical effectiveness.